IMPLEMENTING GENRE PEDAGOGY IN CONTENT INSTRUCTION: LESSONS FROM SWEDEN - Wallden, Robert (Sanata Dharma University Yogyakarta, 2020)
Drawing upon studies conducted in Sweden, this article discusses possibilities and limits of implementing genre pedagogy in content instruction. The wider educational concern is how knowledge of genre and language can be used to promote a deeper engagement with content knowledge. The linguistic theory underpinning genre pedagogy and the pedagogic-practical teaching/learning cycle is explained. Then, two empirical studies of genre-based teaching in Geography in Grade 6 are reviewed, with a particular focus on the texts used as models for the students own writing. The studies show two contrasting sides of genre-based intervention: one in which generic structures and other features of texts are used productively to engage with content knowledge and one in which attention to generic structure and logical connections comes at the expense of the negotiation of content knowledge. The article concludes with recommendations for implementing genre pedagogy.DOI: 10.24071/ijiet.2020.040101